(untitled) (Brazilian Journal of Radiation Sciences, 2018)
The gynecological treatment with High Dose Rate (HDR) Brachytherapy imply deliver dose to the tumor and spare the dose in organs at risk. In this work we apply the recommendations for prescribing dose given by the International Commission of Radiation Units (ICRU) reports 38, 89 and the American Brachytherapy Society (ABS). With both schemes of optimization, recommendation of ICRU 38 or ABS with vaginal point from ICRU 89. Were analyze the dose received by the organs at risk, in this case rectum and bladder and also the irradiated volume for patients that receive HDR brachytherapy treatment. An afterloading technique is applying with a Eckert & Ziegler MultiSource® equipment using a Co-60 source, 30 patients with 4 applications with cervical cancer are planning with HDR brachytherapy. This work analyze 120 single applications with orthogonal images using the treatment planning system (TPS) HDRplus version 3.0.4 through “Auto dwell time determination” optimization method, using the recommendation for optimization dose from the ABS and vaginal point from ICRU 89 . The volume of the isodose curve of prescription is 15% less using ABS recommendation than ICRU 38. The bladder dose is 11% and rectum dose is 21% less using ABS recommendation than ICRU 38. The analysis of dose prescription using ICRU 38 and ABS recommendations in the patients analyzed shows less irradiated volume at the dose prescribed and also less mean dose in rectum and bladder of applications using ABS in contrast with ICRU 38 recommendations.